IDENTIFIKASI GULMA DAN KOMPETISINYA TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays-saccharata Sturt) PADA APLIKASI PUPUK TERPADU - Ayu Dewi Maharani Wahyuningrum; Maria Theresia Darini; Sri Widata (JURNAL ILMIAH AGROUST, 2023)
This study aims to determine the diversity of weeds and their competition with sweet corn and to determine the interaction between organic fertilizer sources and compound fertilizer doses on the growth and yield of sweet corn. The research was conducted from June to December 2022 at Giwangan, Umbulharjo, Yogyakarta. The study was arranged in a RCBD with two factors. The first factor is the source of organic fertilizer, cow manure (K1), chicken manure (K2), and compost (K3). The second factor is the dose of compound fertilizer, the dose of NPK fertilizer 100 kg/ha (N1), 150 kg/ha (N2), and 200 kg/ha (N3). The observed variables consisted of growth variables, such as fresh weight per plant and dry weight per plant and yield variables, such as weed identification, fresh weight per plant, dry weight per plant, corncob weight, yield of sweet corn per hectare, and weed competition index. Data of observation result were analyzed using variance at 5% level, followed by DMRT at α = 5%. The results of the analysis showed that the weeds growing on the sweet corn were weeds of the Poaceae family with an average competition index of 0.38. There was no interaction between the source of organic fertilizer and the dose of NPK compound fertilizer on the growth and yield of sweet corn. Sources of organic fertilizer had no effect on the growth and yield of sweet corn. NPK fertilizer doses had no effect on the growth and yield of sweet corn. Source of organic fertilizer and compound fertilizer doses had no effect on the control on the growth variable but had an effect on the yield variable which was indicated by a decrease in sweet corn yields per hectare of ±38%, from 12.08 tons per ha to 7.21 tons per ha. Keywords : Sweet corn, integrated fertilizer, weed identification, competition index